2012
DOI: 10.14207/ejsd.2012.v1n2p271
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Microbiological Components of Honey Samples Obtained From Ogun State, Southwestern Nigeria

Abstract: There are no detailed studies on the nutritional and microbiological characteristics of honey produced in Ogun State in the Southwestern part of Nigeria. This paper investigated these components in honeys produced from different parts of this state. A total of 10 honey samples per year were collected for the years 2008 -2010. These were separately analyzed for their physical properties, nutritional and microbiological components in the laboratory. The results of the physical properties showed that honey sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 15 publications
3
8
0
Order By: Relevance
“…The ash contents of the natural and the artificial honey were 0.29±0.05% and 0.15±0.09% respectively. These results fall within the limits of <0.6g/100g by Codex Alimentarius Commission, [17] and also agreed with the values of 0.44 to 0.50% reported by Oyeyemi et al [6] and 0.12 to 0.50 by Adenekan et al [11]. This study revealed that natural honey with higher ash content contains more minerals than the artificial honey.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The ash contents of the natural and the artificial honey were 0.29±0.05% and 0.15±0.09% respectively. These results fall within the limits of <0.6g/100g by Codex Alimentarius Commission, [17] and also agreed with the values of 0.44 to 0.50% reported by Oyeyemi et al [6] and 0.12 to 0.50 by Adenekan et al [11]. This study revealed that natural honey with higher ash content contains more minerals than the artificial honey.…”
Section: Resultssupporting
confidence: 91%
“…Traditionally, honey has been used as a medicinal remedy for the treatment of wound, various ailments and diseases [10]. The healing capacity of honey is strongly influenced by the physical and chemical properties of honey [11,12]. Honey comes in a range of colors including white, amber, red, brown and almost black [13].…”
Section: Introductionmentioning
confidence: 99%
“…<20g/100g) stipulated by the Codex Alimentarius Commission and European Union Commission as international standard for honey moisture. The moisture content of the samples falls within the range reported for some Nigerian commercial honeys (Omafuvbe and Akanbi, 2009;Adenekan et al, 2012). Hygroscopic nature, maturity level of honey, hive type, storage and the climatic conditions during the harvesting period are some of the factors affecting moisture content of honey (Ambaye and Mekonen, 2016;Tesfaye et al, 2016).…”
Section: Proximate Analysissupporting
confidence: 71%
“…In the United States, honey has been advocated to be used as a substitute for refined sugars due to its lower glycemic index compared with sucrose (National Honey Board, 2015). Honey not only imparts sweetness but also provides other nutrients such as vitamins and minerals, which improved its nutrient quality (Adenekan et al, 2012). Besides, honey is slightly sweeter than sugars because it contains high fructose content; therefore, a lesser amount of honey can achieve the same sweetness intensity as refined sugar does (National Honey Board, 2015).…”
Section: Introductionmentioning
confidence: 99%